What is practical Islamic ethics, the subject of method and purpose - Mohammad Javad Fallah (اخلاق وحیانی)
Presenting practical Islamic ethics depends on providing a definition based on the foundations and sources of Islamic ethics so that the mechanism of Islamic applied ethics can be built based on that. It is certain that we are faced with new ethical issues in the contemporary era and to solve them we need a field of knowledge related to Islamic sciences, but what mechanism we can use to solve ethical issues depends on providing a definition of applied Islamic ethics. In the selected definition of the subject, purpose and method of applied ethics, these three components will show the distinction of the definition from common views and definitions in applied ethics. The ethical theory of Islam, based on theological and anthropological foundations based on spirituality, depicts practical ethics in a longitudinal system to realize the sublime goals of religion, which is the code of reasonable human life.